A stable aggregate system of silyl ether substituted quinacridone and its aggregation-state changes induced by fluoride-ions: inspiration for a dual guaranteed strategy for probe design. Issue 31 (9th March 2016) - Chen, Peng; Liu, Guo-Jie; Wang, Yuyang; Zhang, Sean Xiao-An
Abstract : Based on the two aggregation-state changes of the THF system of2, a new dual guaranteed strategy for the real-time naked-eye detection of fluoride-ions was developed. Abstract : A sterically hindered silyl ether substituted quinacridone was successfully synthesized and its aggregation behaviors in different solvents were studied. It was demonstrated that the aggregate system of t -butyldiphenylsilyl ether substituted quinacridone in tetrahydrofuran was very stable and its aggregation-state could be tunable by fluoride-ion induced intermolecular force ( e.g. hydrogen bonding and π–π stacking interactions) destructions and a chemical bond cleavage. The two aggregation-state changes of the system could be applied for a new dual guaranteed strategy for real-time naked-eye detection of fluoride-ions, which could provide assurance for both rapid responsive time and extraordinary selectivity.